Sociodemographic Profile and Initiation in Orienteering Running in Brazil: A Sectional Study - Solagaistua de Matos, Fábio (2021)
Introduction: Orienteering running is practiced in Brazil since the 70's. There are difficulties to popularize and consistently increase the number of participants in its main competitions. Thus, it is a sport undervalued about the search for financial resources and aspects of media visibility, in despite that it presents a high degree of attractiveness involving physical and cognitive factors, and having as place of practice natural scenarios, that by themselves would arouse instant interest, as happens in several countries on the European continent.Objective: To describe the sociodemographic characteristics of the Brazilian athlete in Orienteering running and examine the temporality of the beginning of this sport.Methods: Observational, cross-sectional study, in which an online questionnaire was used through Google Forms, containing 68 questions. A total of 638 athletes from Sport Orienteering, of both sexes, participated in the research. Descriptive statistical analyzes were performed in terms of mean, standard deviation and percentage.Results: Practitioners, with ages ranging from 13 to 77(mean 39±13,7) years old, belonged to a higher social class, with higher education, and initiation in sport was over 21 years old.Conclusion: Orienteering practitioners in Brazil are part of a higher socioeconomic group, which differs from the average of the world population. The results indicate that there may be a need for development strategies to promote sports inclusion for people from lower-income social strata.